2021
DOI: 10.47326/ocsat.2021.02.31.1.0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospital Visitor Restrictions during the COVID-19 Pandemic

Abstract: The Ontario COVID-19 Science Advisory Table is a group of scientific experts and health system leaders who evaluate and report on emerging evidence relevant to the COVID-19 pandemic, to inform Ontario's response. Our mandate is to provide weekly summaries of relevant scientific evidence for the COVID-19 Health Coordination Table of the Province of Ontario, integrating information from existing scientific tables, Ontario's universities and agencies, and the best global evidence. The Science Table summarizes its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…One study examining the impact of restrictive visitation policies in Canadian ICUs found communication quality between clinicians and patients was severely diminished by disrupting the flow of information, making grief more challenging, and possibly contributing to moral distress of physicians (20). Importantly, another study found that family members, when using appropriate Personal Protective Equipment, are not significant contributors to hospital spread of COVID-19 infection and prioritizing entry of essential family and caregivers over more general hospital visitors is essential to improve patient care (21). Given the detrimental effect on clinicians and families alike, less restrictive visitor policies would likely ease some of the barriers to communication and therapeutic relationship development across ICU patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…One study examining the impact of restrictive visitation policies in Canadian ICUs found communication quality between clinicians and patients was severely diminished by disrupting the flow of information, making grief more challenging, and possibly contributing to moral distress of physicians (20). Importantly, another study found that family members, when using appropriate Personal Protective Equipment, are not significant contributors to hospital spread of COVID-19 infection and prioritizing entry of essential family and caregivers over more general hospital visitors is essential to improve patient care (21). Given the detrimental effect on clinicians and families alike, less restrictive visitor policies would likely ease some of the barriers to communication and therapeutic relationship development across ICU patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Restricting hospital visits during the COVID-19 pandemic's rst wave had the following aims: (1) preventing the transmission of SARS-CoV-2 from the community into acute hospitals (infecting healthcare staff and patients), (2) preventing transmission in the other direction (infecting visitors), and (3) maintaining adequate supplies of personal protective equipment (40). At the pandemic's onset, potential visitor-related COVID-19 outbreaks were considered a substantial risk and, thus, all types of visits were restricted, despite a lack of scienti c evidence linking visitors to SARS-CoV-2 transmission (41,42).…”
Section: Visiting Restrictions During the Covid-19 Pandemicmentioning
confidence: 99%
“…Clinicians recognize the importance of patient relationships with, and caregiving by, family in hospitals, nursing homes, and long-term care (LTC) settings. 2,3 Although institutional visitor policies had become more flexible in response to patient and family needs over time, 4,5 the COVID-19 pandemic reversed this progress, often closing doors to family/ caregivers.…”
Section: Introductionmentioning
confidence: 99%